Color revolution: toward ultra-wide color gamut displays. (4th March 2021) - Wen, Zuoliang; Zhou, Ziming; Liu, Haochen; Wang, Zhaojin; Li, Xiang; Fang, Fan; Wang, Kai; Teo, Kie Leong; Sun, Xiao Wei
Abstract: With the economic and social developments, the demand for higher quality displays has always remained strong. The emerging 8K displays represent an advancement of ultra-high resolution. Other parameters such as the contrast ratio and viewing angle were all improved significantly. Here, we would like to address the recent efforts in the color (color gamut) of displays toward an ultra-wide color gamut, which we call the 'color revolution'. In the past few years, fluorescent semiconductor quantum dots, quantum rods, fluorescent perovskite nanocrystals, and nanoplatelets with narrow emission have been discovered, and have been explored in display technologies as photoluminescent enhancement films, color convertors, or electroluminescent emissive layers. As a result, the color gamut of display technologies was broadened remarkably, enabling the color revolution. Here, we provide a review of this exciting progress iin the color revolution.